Anti-pseudomonas activity of essential oil, total extract, and proanthocyanidins of Pinus eldarica Medw. bark - Masoud Sadeghi; Behzad Zolfaghari; Ali Jahanian-Najafabadi; Seyed Reza Abtahi (Wolters Kluwer Medknow Publications, 2016)
Pinus eldarica Medw. (Iranian pine) is native to Transcaucasian region and has been vastly planted in Iran, Afghanistan, and Pakistan. Various parts of this plant have been widely used in traditional medicine for the treatment of various diseases including infectious conditions (e.g. infectious wounds). In this study we aimed to investigate the antibacterial activity of P. eldarica bark extract, essential oil and proanthocyanidins on three important bacteria, Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. Antibacterial analysis was performed using standard disk diffusion method with different concentrations of essential oil, bark total hydroalcoholic extract, and bark proanthocyanidins (0.5, 1, 2 and 3 mg/ml). After incubation at 37 °C for 24 h, the antibacterial activity was assessed by measuring the zone of growth inhibition surrounding the disks. The results indicated that the essential oil, total hydroalcoholic extract, and proanthocyanidins of the bark of the P. eldarica were effective against the gram negative bacteria, P. aeruginosa, and significantly inhibited its growth in disk diffusion method (P<0.001) of which the essential oil had the most potent inhibitory effect. However, none of the bark preparations could significantly inhibit the growth of S. aureus or E. coli. Our findings showed that P. eldarica bark components have significant anti-pseudomonas activity having potentials for new sources of antibacterial agents or antibacterial herbal preparations.